Enhancing self-awareness, positive emotions and personal effectiveness : a mixed method study of growth-oriented outcomes in higher education - Zuhrah Beevi,; Tzyy, Yang Gan; Hall, Deborah Ann (Penerbit Universiti Kebangsaan Malaysia, 2021)
Positive education increases students’ well-being, personal effectiveness, and positive emotions and subsequently prepares them with skills (e.g., leadership) to enhance their careers. The present study explores students’ experiences in engaging in the positive education programme in an institution of higher learning. The Self-empowerment and Social Responsibility course was compulsory for year one undergraduate students. A total of 350 students completed pre- and post-intervention measures of happiness and life satisfaction. Eleven students participated in a semi-structured interview. Interviews were transcribed, and the content was analysed, following which themes were extracted. Although the quantitative data showed no change, the interview results found that students described the course as unique and a positive step in helping their careers. The selected students perceived that the course increased students’ self-awareness, developed their soft skills and positive emotions (e.g., happiness). Implementing a positive education programme in higher institutions provides students with the additional tool to be well-rounded graduates as they enter the job market.